Plus Ultra: Juridical Analysis of Space Resources Utilization Mechanisms for Indonesia’s Future Regulation - Hiawananta, Ozha Tiwa; Masyithoh, Novita Dewi; Ardila, Arina Hukmu (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The current development of outer space has reached a new beginning, marked by many space company leveraging the opportunities of the space economy. Outer space itself is governed by a set of international treaties known as the Corpus Juris Spatialis. However, with the rapid advancement of space commercialization, the provisions of the Corpus Juris Spatialis are deemed unable to accommodate all existing phenomena. Therefore, many regulatory frameworks are currently being established to fill the gaps in the Corpus Juris Spatialis, one of which is domestic law. Along with advancements in space technology in spacefaring nations such as the United States and Japan alongs with non space firing nations such as Luxembourg, and the United Arab Emirates, domestic regulations have been enacted to permit private ownership of extracted space resources. On the other hand, Indonesia, as a non-spacefaring nation, currently lacks a legal framework for space commercialization related to the utilization of outer space resources in space mining activities. The objectives of this research are, first, to examine the international legal framework, national laws, and those created by international organizations related to the utilization of outer space governance. Second, this research will attempt to provide a new perspective on a comprehensive and responsible national regulatory framework for commercialization. This study used a normative juridical method with a comparative and conceptual approach to evaluate regulatory mechanisms, particularly the application of the